2014
DOI: 10.1080/07350015.2014.897954
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic Theory for the QMLE in GARCH-X Models With Stationary and Nonstationary Covariates

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 42 publications
1
44
0
Order By: Relevance
“…When the covariates are integrated, Han and Park (2012) study the maximum likelihood estimation of the parameters in the ARCH and GARCH models. A recent paper by Han and Kristensen (2014) further considers the quasi maximum likelihood estimation in the GARCH-X models with stationary and nonstationary covariates. We next consider the general Harris recurrent Markov process {X t } and use a robust estimation method for model (4.1).…”
Section: Nonlinear Heteroskedastic Regressionmentioning
confidence: 99%
“…When the covariates are integrated, Han and Park (2012) study the maximum likelihood estimation of the parameters in the ARCH and GARCH models. A recent paper by Han and Kristensen (2014) further considers the quasi maximum likelihood estimation in the GARCH-X models with stationary and nonstationary covariates. We next consider the general Harris recurrent Markov process {X t } and use a robust estimation method for model (4.1).…”
Section: Nonlinear Heteroskedastic Regressionmentioning
confidence: 99%
“…Actually, even if practitioners often add exogenous variables to volatility models, the probabilistic properties and the statistical inference of ARCH models with exogenous variables have not been yet extensively studied. Notable exceptions are the papers of Han (2013), Han and Kristensen (2014) and Han andPark (2012, 2014), which studied the inference of the GARCH(1,1) model augmented by an additional covariate which can be persistent. A common assumption to all the references previously given in this section, is that the true value of the parameter belongs to the interior of the parameter space.…”
Section: The Objectivesmentioning
confidence: 99%
“…For the GARCH-type models, it is usual to assume the stronger assumption that (η t ) is iid (0, 1). Note, however, that Escanciano (2009) and Han and Kristensen (2014) employed A2. The advantage of using A2 is that (2) becomes a semistrong model, that can be satisfied for different σ-fields F t , corresponding for example to different sequences of exogenous variables (x t ).…”
Section: Strong Consistency Of the Qmlementioning
confidence: 99%
See 1 more Smart Citation
“…The theoretical properties of the QMLE in the GARCH model need to be developed further, especially in statistical applications, to include situations where these sorts of moment conditions are not satis ed. Han and Kristensen (2014) [15] applied the asymptotic properties of Gaussian QMLE to the GARCH model with an additional explanatory variable, and showed that the QMLE of the parameters for the volatility equation is consistent and mixed-normally distributed in large samples.…”
Section: Introductionmentioning
confidence: 99%